Amelioration of Hepato-renal Impairment by Natural Chelators in Lead-induced Poisoning in Rats - Nausheen, Quadri Neha; Ali, Syed Ayaz; Syed, Shoaeb Mohammad; Patave, Tarannum Rashid (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Hepato-Renal impairment refers to renal dysfunction in a liver compromised state concerning lead metal exposure. Natural chelators (marine source) have potent chelating properties claiming to ameliorate hepato-renal dysfunction in heavy metal toxicity Material and Methods: A total of 42 male albino Wistar rats weighing between 200 to 250 g were categorised into seven groups (n=6). Except for the first group (control), which received sodium-acetate (1,000 mg/L in drinking water), all of the groups received lead acetate 0.4 mg/kg body weight per oral (p.o). Second-group is the negative control group (toxic), the third and fourth received Chitosan and Chitosamine 0.2 g/kg (p.o) respectively. Ethylene diaminetetra acetic acid (EDTA) 495 mg/kg (p.o) was given to the fifth, sixth, and seventh groups, whereas Chitosan and Chitosamine [0.2 g/kg (p.o)] were given to the sixth and seventh groups, respectively. Results: There is statistical significant increase in atherogenic indices, serum lipid profile, renal tissue oxidativestress, renal function biomarkers, kidney weights, and decrease in body weights of experimental animals in the toxic as compared to control whereas these values ameliorated in treatment groups as compared to toxic group. Histopathology of toxic group kidneys revealed histologic and pathological changes in nephrons along with dyslipidemia which healed to normal architecture and analytical values in treatment groups. Thus, the study confirms the nephro protective effect and improvement of dyslipidemia as a consequence of hepato-renal impairment by natural chelators. Conclusion: The natural chelators have hepatic and nephro protective effect in lead metal induced poisoning.
Keywords: Lead Toxicity; Nephrotoxicity; Chitosan; Chitosamine; Chelation; Atherogenic; indices; Oxidative Stress